INTERNET OF THINGS (IOT) AS A DRIVER OF THE INDUSTRIAL REVOLUTION4.0 TOWARDS ECONOMY 5.0 - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The Internet of Things (IoT) is a key element in driving the Industrial Revolution 4.0 and the transition to Economy 5.0, by utilising connected devices to collect and analyse data to improve efficiency and productivity across various sectors. In the context of Industry 4.0, IoT plays a role in automating production processes, optimising resource management, and facilitating predictive maintenance through real-time data analysis. IoT not only reduces downtime and operational costs, but also improves product quality and reliability. As we move towards Economy 5.0, IoT goes beyond industrial efficiency and focuses on achieving greater social welfare. It supports the creation of a more inclusive and sustainable ecosystem, from remote patient health monitoring to energy-efficient smart city management. The positive impact of IoT spans various aspects of life, contributing to the improvement of quality of life and the broader well-being of society. However, the implementation of IoT in industry and the economy faces various challenges, including data security and privacy issues, device interoperability, and adaptive regulations. Cooperation between the government, private sector, and society as well as investment in education and relevant infrastructure are needed to overcome these obstacles. Thus, IoT can continue to play a role as a driver of innovation and quality of life improvement, supporting the achievement of the Industrial Revolution 4.0 and Economy 5.0.